2020
DOI: 10.3390/su12052094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contemporary Land Use Types and Conversions from Wetland to Paddy Field or Dry Land on Soil Organic Carbon Fractions

Abstract: Soil organic carbon (SOC) concentration is closely related to soil quality and climate change. The objectives of this study were to estimate the effects of contemporary land use on SOC concentrations at 0-20 cm depths, and to investigate the dynamics of SOC in paddy-field soil and dry-land soil after their conversion from natural wetlands (20 and 30 years ago). We investigated the dissolved organic carbon (DOC), light fraction organic carbon (LFOC), heavy fraction organic carbon (HFOC), and other soil properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…The SOC and labile organic C had the strongest effects on the variability of soil enzyme activities by RDA (Figure 4). Supporting evidence, after wetland conversion, the DOC content decreased in paddy fields and dryland (Zhao et al, 2020). Wang et al (2013) showed that BGL and NAG decreased after conversion from native wetland to soybean cropland in a chronosequence over 24 years, and soil enzyme activities were highly correlated with DOC (r = 0.59, p = 0.01 for NAG; r = 0.89, p < 0.001 for BGL).…”
Section: Effect Of Soil C Cycle-related Enzyme Activities On Land Use...mentioning
confidence: 86%
“…The SOC and labile organic C had the strongest effects on the variability of soil enzyme activities by RDA (Figure 4). Supporting evidence, after wetland conversion, the DOC content decreased in paddy fields and dryland (Zhao et al, 2020). Wang et al (2013) showed that BGL and NAG decreased after conversion from native wetland to soybean cropland in a chronosequence over 24 years, and soil enzyme activities were highly correlated with DOC (r = 0.59, p = 0.01 for NAG; r = 0.89, p < 0.001 for BGL).…”
Section: Effect Of Soil C Cycle-related Enzyme Activities On Land Use...mentioning
confidence: 86%
“…There was a significant difference in SOC content between PF and DL, with DL showing an overall 37.1% lower SOC content than PF (Table 2). Several mechanisms may explain the higher SOC in PF (Chen et al, 2021; Kögel‐Knabner et al, 2010; H. Zhang et al, 2016; Zhao et al, 2020): (1) straw return is a common practice in paddy lands in China, with the result of a higher amount of organic matter in the soil; (2) the higher SOC content in PF could be linked to the lower decomposition rate of organic material in flooding condition; (3) generally higher contents of Fe oxyhydrates in PF, which can facilitate soil C sequestration through the large surface area. Although no significant difference was found between PF and VF, VF had an overall 7.5% lower SOC than PF.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may explain the higher SOC in PF (Chen et al, 2021;Kögel-Knabner et al, 2010;H. Zhang et al, 2016;Zhao et al, 2020): (1) straw return is a common practice in paddy lands in China, with the result of a higher amount of organic matter in the soil;…”
Section: Comprehensive Effects Of Different Farmland Utilization Type...mentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities play a substantial role in the transport of riverine DOC, e.g., acid deposition, nitrogen deposition, and agricultural activities [27][28][29][30]. In particular, land use and cover change, fire, and forest species greatly affect the variation of SOCs, which further alter the riverine DOC amount [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%